The efficacy of thermotherapy to treat cutaneous leishmaniasis in Colombia: a comparative observational study in an operational setting (2009)
An open label, comparative study to compare the efficacy of thermotherapy to meglumine antimoniate in treating cutaneous leishmaniasis patients in an operational context was carried out in Chaparral, Colombia. After enrollment patients were followed-up for up to 100 days. Per protocol and intention-to-treat cure rates for 47 patients treated using thermotherapy (one-time 50 degrees C applications for 30s) were 100 and 19%, respectively. Per protocol and intention-to-treat cure rates for meglumine antimoniate (20 mg/kg body weight administered intramuscularly for 21 d) were 78 and 23%, respectively.